Analysis of the Virulence Profile and Phenotypic Features of Typical and Atypical Enteroaggregative Escherichia coli (EAEC) Isolated From Diarrheal Patients in Brazil - Dias, Regiane C. B.; Tanabe, Rodrigo H. S.; Vieira, Melissa A.; Cergole-Novella, Maria C.; dos Santos, Luís F.; Gomes, Tânia A. T.; Elias, Waldir P.; Hernandes, Rodrigo T. (Frontiers in Cellular and Infection Microbiology, 2020)
Enteroaggregative Escherichia coli (EAEC) is an important agent of acute and persistent diarrhea in children and adults worldwide. Here we report a characterization of 220 EAEC isolates, 88.2% (194/220) of which were typical and 11.8% (26/220) were atypical, obtained from diarrheal patients during seven years (2010-2016) of epidemiological surveillance in Brazil. The majority of the isolates were assigned to phylogroups A (44.1%, 97/220) or B1 (21.4%, 47/220). The aggregative adherence pattern was detected in 92.7% (204/220) of the isolates, with six of them exhibiting AA concomitantly with a chain-like adherence pattern; and agg5A and agg4A were the most common adhesin-encoding genes, which were equally detected in 14.5% (32/220) of the isolates. Each of 12 virulence factor-encoding genes (agg4A, agg5A, pic, aap, aaiA, aaiC, aaiG, orf3, aar, air, capU, and shf) were statistically associated with typical EAEC (P<0.05). The genes encoding the newly described aggregate-forming pili (AFP) searched (afpB, afpD, afpP, afpA2), and/or its regulator (afpR), were exclusively detected in atypical EAEC (57.7%, 15/26), and showed a significant association with this subgroup of EAEC (P<0.001). In conclusion, we presented an extensive characterization of the EAEC circulating in the Brazilian settings and identified the afp genes as putative markers for increasing the efficiency of atypical EAEC diagnosis.